Origins of the Apple: The Role of Megafaunal Mutualism in the Domestication of Malus and Rosaceous Trees - Spengler, Robert Nicholas (Frontiers in Plant Science, 2019)
The apple (Malus domestica [Suckow] Borkh.) is one of the most economically and culturally significant fruits in the world today, and it is grown in all temperate zones. With over a thousand landraces recognized, the modern apple provides a unique case study for understanding plant evolution under human cultivation. Recent genomic and archaeobotancial studies have illuminated parts of the process of domestication in the Rosaceae family. Interestingly, these data seem to suggest that rosaceous arboreal crops did not follow the same pathway towards domestication as other domesticated, especially annual, plants. Unlike in cereal crops, tree domestication appears to have been rapid and driven by hybridization. Apple domestication also calls into question the concept of centers of domestication and human intentionality. Studies of arboreal domestication also illustrate the importance of fully understanding the seed dispersal processes in the wild progenitors when studying crop origins. Large fruits in Rosaceae evolved as a seed-dispersal adaptation recruiting megafaunal mammals of the late Miocene. Genetic studies illustrate that the increase in fruit size and changes in morphology during evolution in the wild resulted from hybridization events and were selected for by large seed dispersers. Humans over the past three millennia have fixed larger-fruiting hybrids through grafting and cloning. Ultimately, the process of evolution under human cultivation parallels the natural evolution of larger fruits in the clade as an adaptive strategy, which resulted in mutualism with large mammalian seed dispersers (disperser recruitment).